Produção científica sobre a assistência de enfermagem em hipertensão arterial sistêmica na atenção primária - Pedrino, Helen Cristina (2010)
Due to the importance of health care research in improving the health conditions of populations and in framing/planning of public policies and because of the existing gap between research and production activities, the purpose of this study was to look into the scientific literature about primary care nursing of hypertensive patients with regard to promoting health and avoiding complications, to reveal how professionals use these materials in their practices, and to analyze their social representations of the science, technology, and innovation permeating these activities. The first phase of this exploratory-analytical study comprised a bibliographical investigation at SciELO, using the Vantage Point software, and an analysis of the data based on references to health technology (101 studies were identified, from 58 research-universities). Subsequently, family care nurses from São Carlos, Brazil, were interviewed; their answers were systematized with the help of ALCESTE 4.5 and the emerging categories were analyzed in light of the Social Representations Theory. It was observed that most studies were of a descriptive nature, almost evenly divided into qualitative and quantitative designs. Most of them were carried out at public universities, made use of surveys and bibliographical research as technical procedures, and focused on hard-soft technologies. In the care of hypertensive patients, the 14 respondents used mainly soft nursing technologies, e.g., welcoming and relations, and pointed to the Family Health Program as the process facilitator par excellence, because of its focus on the person as opposed to the illness. Some of the reported difficulties were: shortage of human resources and the still prescriptive education of health personnel. This study also pointed to the rising number of articles on nursing in this field in the past three years and indicated that the nurses involved in the care of hypertensive patients regularly resorted to scientific knowledge found in the literature, adapting it to their realities, but were uninterested in producing it.